Optimizing deposition regimes to fabricate VO2/TiO2/c-Al2O3 thin films for active metasurfaces - M. E. Kutepov; V. E. Kaydashev; D. V. Stryukov; A. S. Konstantinov; A. S. Mikheykin; A. V. Nikolskiy; A. T. Kozakov; A. D. Morozov; M. A. Kashchenko; G. V. Alymov; E. M. Kaidashev (Journal of Advanced Dielectrics)
Decreasing the scale of vanadium dioxide (VO2) structures is one of the ways to enhance the switching speed of the material. We study the properties of VO2 films of altered thicknesses in the range of 20–170[Formula: see text]nm prepared on c-sapphire substrates with a TiO2 sublayer by pulsed laser deposition (PLD) method. The synthesis regime to design a TiO2 film was preliminarily optimized based on XRD data. XRD patterns reveal an epitaxial growth of the VO2 films with distortion of the monoclinic cell to hexagonal symmetry. The positions of the lattice vibration modes in Raman spectra are similar to those in bulk VO2 when the film thickness is greater than [Formula: see text][Formula: see text]nm. For VO2 films thicker that [Formula: see text][Formula: see text]nm, a lattice strain results in the modes’ positions and intensity change. However, the electrically triggered transition in a [Formula: see text][Formula: see text]nm thick VO2 film reveals forward and reverse switching times as short as 20[Formula: see text]ns and 400[Formula: see text]ns, correspondingly.